Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1006/jcta.2002.3277
|View full text |Cite
|
Sign up to set email alerts
|

On Four Colored Sets with Nondecreasing Diameter and the Erdős–Ginzburg–Ziv Theorem

Abstract: A set X; with a coloring D: X ! Z m ; is zero-sum if P x2X DðxÞ ¼ 0: Let f ðm; rÞ (let f zs ðm; 2rÞ) be the least N such that for every coloring of 1; . . . ; N with r colors (with elements from r disjoint copies of Z m ) there exist monochromatic (zero-sum) m-element subsets B 1 and B 2 ; not necessarily the same color, such that (a) maxðB 1 Þ À minðB 1 Þ4maxðB 2 Þ À minðB 2 Þ; and (b) maxðB 1 Þ5minðB 2 Þ: We show that f zs ðm; 4Þ ¼ f ðm; 4Þ: # 2002 Elsevier Science (USA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Any Ramsey theory problem has a corresponding zero-sum version obtained by replacing colorings using two colors with colorings using the elements of Z m and looking for zero-sum substructures rather than monochromatic ones. Through a slightly more complicated way, Ramsey theory questions involving more than two colors also have a corresponding zero-sum version [7], [34], [35]. If m is chosen to be the size of the particular substructure in question, then the zero-sum Ramsey number always gives an upper bound on the monochromatic Ramsey number, but, perhaps unexpectedly, the two numbers were in many cases equal.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Any Ramsey theory problem has a corresponding zero-sum version obtained by replacing colorings using two colors with colorings using the elements of Z m and looking for zero-sum substructures rather than monochromatic ones. Through a slightly more complicated way, Ramsey theory questions involving more than two colors also have a corresponding zero-sum version [7], [34], [35]. If m is chosen to be the size of the particular substructure in question, then the zero-sum Ramsey number always gives an upper bound on the monochromatic Ramsey number, but, perhaps unexpectedly, the two numbers were in many cases equal.…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
“…The following references also contain several theorems that are often quite useful when used in conjunction with Corollary 1. Corollary 1 was used to establish a four-color zero-sum generalization that was the next open case in a conjecture of Bialostocki, Erdős, and Lefmann [7], [35]. Relaxing the structure from the aforementioned problem, a zero-sum generalization was obtained, with the aid of the Olson case of Corollary 1, for two, three, four and five colors [34].…”
Section: Introduction and Main Resultsmentioning
confidence: 98%
“…, m; r) in [3], where they determined that f (m, m; 2) = 5m − 3, that f (m, m; 3) = 9m − 7 and that (1) 8m − 4 ≤ f (m, m, m; 2) ≤ 10m − 6, as well as giving asymptotic bounds for t = 2. The problem was motivated in part by zero-sum generalizations in the sense of the Erdős-Ginzburg-Ziv Theorem [6] [9, Theorem 10.1] (see [2] [3] [7] for a short discussion of zero-sum generalizations, including definitions). Subsequently, Bollobás, Erdős, and Jin obtained improved results for m = 2, showing that 4r − log 2 r + 1 ≤ f * (2, 2; r) ≤ 4r + 1 and f * (2, 2; 2 k ) = 4 · 2 k + 1, as well as giving improved asymptotic bounds for t and r when m = 2.…”
Section: Introductionmentioning
confidence: 99%
“…They also introduced a notion of zero-sum generalization for Ramsey-type problems involving arbitrary r-colorings (not just 2-colorings), and showed that the corresponding 3-color version of the nondecreasing diameter problem for two m-sets also zero-sum generalized. Recently, the four color case was shown to zero-sum generalize [24], but the cases with r > 4 remain open and difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we introduce and study the functions f j (m, 2) and f j (m, Z m ) with j < m, thus studying the nondecreasing diameter problem by varying the notion of diameter by the parameter j. One of our main tools is an improvement to a recent generalization (Theorem 2.7) of results of Mann [29], Olson [31], Bollobás and Leader [10], and Hamidoune [26], that was developed by the first author [23] while studying the original nondecreasing diameter problem for four colors [24].…”
Section: Introductionmentioning
confidence: 99%